Splenic vascularization: its relation to conservative surgery - Doassans, Carlos; Torres, Marcos; Pressa, Carlos (Cirugía del Uruguay, 1984)
Valuation of the intrasplenic arterial distribution. Compared in a series in the.dog, in an adult man and a suckling baby. No clival slope couo be detected and author conclu• des performance of segmentary resection is not possible.